Female leadership and workplace climate - Sule Alan; Gozde Corekcioglu; Mustafa Kaba; Matthias Sutter (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
At the very heart of a healthy work environment lies the quality of social interactions among colleagues and between leaders and subordinates. This column investigates the role of gender in transforming the relational atmosphere in the workplace. The results show that a fairer representation of female leadership may have benefits beyond efficiency and social justice concerns by creating a more inclusive and less segregated workplace, one in which employees and leaders form stronger inter-gender ties and female employees exhibit less voluntary quits.
Keywords: 330